TINJAUAN HUKUM ISLAM TERHADAP PROBLEMATIKA HEWAN KURBAN - Nasution, Wilda Rahma (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
Sacrifice is one of the worship in Islam that has certain rules as stipulated in Islamic law. Thus all its rules have been outlined by the law of sharia. But until now the problems of sacrifice are still ongoing, such as sacrifices that individuals count while Eid al-Adha sacrifices are not the same as akikah and even zakat fitrah that individuals can count, then choose not to sacrifice or postpone sacrifice because the sacrificial animals that are desired to be slaughtered during the feast of sacrifice are cows, not goats. So this study aims to determine the limit on the number of people who sacrifice for one sacrificial animal and the animal that is mainly slaughtered as a sacrificial animal. Research is carried out with normative legal research methods also called doctrinal legal research, where in this type of legal research the law is conceptualized as what is written in laws and regulations (law in books) or law is conceptualized as rules or norms that are a benchmark for human behavior aimed at solving legal issues faced deemed appropriate. As for the results of the study, it can be concluded that one goat is enough for one person, it is not legal for more than one person. One camel and a cow suffice for seven people. Association in sacrificial animals cannot be separated from two conditions, namely association in terms of merit and association in terms of ownership. As for the main animals to be sacrificed in terms of type, the first opinion is according to the order of camels, cows, and goats. The second opinion is goat, cow, and camel. Meanwhile, when viewed from the criteria of animals, the most important thing to be used as a sacrifice is a male animal of perfect quality.